1982
DOI: 10.1126/science.6815801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Protein That Purifies with the Scrapie Prion

Abstract: Purification of prions from scrapie-infected hamster brain yielded a protein that was not found in a similar fraction from uninfected brain. The protein migrated with an apparent molecular size of 27,000 to 30,000 daltons in sodium dodecyl sulfate polyacrylamide gels. The resistance of this protein to digestion by proteinase K distinguished it from proteins of similar molecular weight found in normal hamster brain. Initial results suggest that the amount of this protein correlates with the titer of the agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
733
1
23

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,191 publications
(768 citation statements)
references
References 22 publications
11
733
1
23
Order By: Relevance
“…The notion that the infectious disease agent in TSE could be devoid of nucleic acids and primarily exists of protein, the so-called protein-only hypothesis, was first advanced in the 1960s based on experimental observations [1] and theory [2]. Prusiner and colleagues later showed that a particular protein was indeed required for infectivity [3][4][5]. Based on the name given to such a protein-based nucleic-acid free agent, a proteinaceous infectious particle or prion, the protein was called the prion protein (PrP).…”
Section: Introductionmentioning
confidence: 99%
“…The notion that the infectious disease agent in TSE could be devoid of nucleic acids and primarily exists of protein, the so-called protein-only hypothesis, was first advanced in the 1960s based on experimental observations [1] and theory [2]. Prusiner and colleagues later showed that a particular protein was indeed required for infectivity [3][4][5]. Based on the name given to such a protein-based nucleic-acid free agent, a proteinaceous infectious particle or prion, the protein was called the prion protein (PrP).…”
Section: Introductionmentioning
confidence: 99%
“…SAF consist primarily of the disease-specific SAFprotein [also referred to as protease-resistant protein or prion protein, PrP (Bolton et al, 1982;McKinley et al, 1983)] (Diringer et al, 1983a;Barry et al, 1985;DeArmond et al, 1985;Merz et al, 1987;Wiley et al, 1987). This amyloid protein is derived from a highly conserved host-encoded precursor, a cellular glycoprotein (tool.…”
Section: Introductionmentioning
confidence: 99%
“…Back in 1982, biochemist Stanley Prusiner, now director of the Institute for Neurodegenerative Diseases at the University of California, San Francisco, showed that a class of diseases called transmissible spongiform encephalopathies was caused not by a microbe, but by prion protein (PrP) 5 . PrP exists in a healthy form, but causes disease when it misfolds into shapes that induce other PrP molecules to do the same -and so becomes self propagating.…”
Section: The Protein Pathogenmentioning
confidence: 99%